2022
DOI: 10.1371/journal.pone.0264639
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices related to COVID-19 among poor and marginalized communities in central India: A cross-sectional study

Abstract: COVID-19 has led to unprecedented challenges and requires local and global efforts for its mitigation. Poor and marginalized populations are more vulnerable to the health, social and economic effects of the pandemic. The objective of this study was to know about the knowledge, attitude and practices towards COVID-19 among poor and marginalized communities in central India and the factors associated with them so that effective risk communication messages can be designed and community engagement needs and strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, it was noted that poor knowledge about COVID-19 and negative attitudes toward the disease were associated with inadequate preventive behaviors. 6,27,28 Such outcomes confirm previous studies such as those by Nguyen et al 6 and another research conducted by Doan et al, 29 who found similar trends among Vietnamese populations. Our results also align with findings from Huynh et al's 5 research (2020) on outpatients at Second District Hospital, Ho Chi Minh City.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, it was noted that poor knowledge about COVID-19 and negative attitudes toward the disease were associated with inadequate preventive behaviors. 6,27,28 Such outcomes confirm previous studies such as those by Nguyen et al 6 and another research conducted by Doan et al, 29 who found similar trends among Vietnamese populations. Our results also align with findings from Huynh et al's 5 research (2020) on outpatients at Second District Hospital, Ho Chi Minh City.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, it was noted that poor knowledge about COVID-19 and negative attitudes toward the disease were associated with inadequate preventive behaviors. 6 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…IVR has been shown to be acceptable and useful in qualitative studies and a mobile phone-based IVR health information and surveillance system in Ghana was demonstrated to support user healthcare decision-making and disease awareness [ 36 ]. IVR is being explored as a data collection tool to reach groups that are often missed using conventional techniques with promising initial results [ 37 ].…”
Section: Introductionmentioning
confidence: 99%